Gender‐biased kidney damage in mice following exposure to tobacco cigarette smoke: More protection in premenopausal females. Issue 2 (24th January 2020) - Kaplan, Abdullah; Abidi, Emna; Habeichi, Nada J.; Ghali, Rana; Alawasi, Hiam; Fakih, Christina; Zibara, Kazem; Kobeissy, Firas; Husari, Ahmad; Booz, George W.; Zouein, Fouad A.
Abstract: Multiple clinical studies documented renal damage in chronic cigarette smokers (CS) irrespective of their age and gender. Premenopausal female smokers are known to exert a certain cardiovascular and renal protection with undefined mechanisms. Given the multiple demographic variables within clinical studies, this experimental study was designed to be the first to assess whether gender‐biased CS‐induced kidney damage truly exists between premenopausal female and age‐matched C57Bl6J male mice when compared to their relative control groups. Following 6 weeks of CS exposure, cardiac function, inflammatory marker production, fibrosis formation, total and glomerular ROS levels, and glomerulotubular homeostasis were assessed in both genders. Although both CS‐exposed male and female mice exhibited comparable ROS fold change relative to their respective control groups, CS‐exposed male mice showed a more pronounced fibrotic deposition, inflammation, and glomerulotubular damage profile. However, the protection observed in CS‐exposed female group was not absolute. CS‐exposed female mice exhibited a significant increase in fibrosis, ROS production, and glomerulotubular alteration but with a pronounced anti‐inflammatory profile when compared to their relative control groups. Although both CS‐exposed genders presented with altered glomerulotubular homeostasis, the alteration phenotype between genders was different. CS‐exposed males showed a significant decrease in Bowman's space along with reduced tubular diameter consistent with an endocrinization pattern of chronic tubular atrophy, suggestive of an advanced stage of glomerulotubular damage. CS‐exposed female group, on the other hand, displayed glomerular hypertrophy with a mild tubular dilatation profile suggestive of an early stage of glomerulotubular damage that generally precedes collapse. In conclusion, both genders are prone to CS‐induced kidney damage with pronounced female protection due to a milder damage slope. Abstract : Mice of both genders exposed to 6 weeks of tobacco cigarette smoke are prone to kidney damage with pronounced female protection due to a milder damage slope.